2020
DOI: 10.1097/md.0000000000020216
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cervical spondylotic radiculopathy with posterior percutaneous endoscopic cervical discectomy

Abstract: To determine the short-term clinical outcomes of single-segment cervical spondylotic radiculopathy treated with posterior percutaneous endoscopic cervical discectomy (PPECD). Data of a total of 24 patients who underwent PPECD and local anesthesia for single-level segmental cervical spondylotic radiculopathy between March 2016 and December 2017 were reviewed. The Japanese Orthopaedic Association, visual analog scale (VAS), and neck disability index scores at preoperative 1 day, postoperative 1 day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Owing to the large difference in sample sizes of the studies on PPEKF, the overall postoperative complications greatly varied. Some studies did not report any complications, 12 , 26 , 28 but one study reported an overall complication rate as high as 14.3%. 16 However, the specific proportions of several common complications showed significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the large difference in sample sizes of the studies on PPEKF, the overall postoperative complications greatly varied. Some studies did not report any complications, 12 , 26 , 28 but one study reported an overall complication rate as high as 14.3%. 16 However, the specific proportions of several common complications showed significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of endoscopic technique has made the posterior cervical foraminotomy (PCF) minimally invasive, avoiding the injury of the large surgical incision to the paravertebral muscles. 11,12 So posterior percutaneous endoscopic keyhole foraminotomy (PPEKF) has become an alternative technique to open discectomy in the posterior cervical approach, especially for single-level unilateral cervical radiculopathy. 13,14 Few previous studies and meta-analysis have compared the therapeutic effects of ACDF and PCF in the treatment of cervical radiculopathy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to our intraoperative experience of PPECD, herniated discs with less than 33.785° of CDHCA were commonly located at infra‐axillary or anterior region of the nerve root. This anatomical relationship between the herniated disc and nerve root requires an extended excision of ligamentum flavum, which consequently leads to more bleeding and influences endoscopic visuality 24 . In addition, there exists an underlying physiological relationship between the variation of CDHCA and motion of cervical cord.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spondylotic radiculopathy (CSR) is often caused by nerve compression due to cervical disc herniation, intervertebral foramen stenosis, and hyperplastic osteophytes 1 , 2 . Its main symptoms include pain in the neck and upper limbs, with or without numbness, and with surgical treatment needed in severe cases 3 . Since its first proposal by Smith and Robinson in 1955 4 , anterior cervical discectomy and fusion (ACDF) has been regarded as the gold standard for CSR treatment.…”
Section: Introductionmentioning
confidence: 99%